2016
DOI: 10.1371/journal.pone.0149303
|View full text |Cite
|
Sign up to set email alerts
|

A Systems Biology Approach to the Coordination of Defensive and Offensive Molecular Mechanisms in the Innate and Adaptive Host–Pathogen Interaction Networks

Abstract: Infected zebrafish coordinates defensive and offensive molecular mechanisms in response to Candida albicans infections, and invasive C. albicans coordinates corresponding molecular mechanisms to interact with the host. However, knowledge of the ensuing infection-activated signaling networks in both host and pathogen and their interspecific crosstalk during the innate and adaptive phases of the infection processes remains incomplete. In the present study, dynamic network modeling, protein interaction databases,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 56 publications
1
7
0
Order By: Relevance
“…Together, these two recent studies converge in illustrating Graham and Tate's conclusion that the sooner the immune system launches, the greater the chances the host has of survival (30). It is also consistent with recent systems biology approach suggesting that early pathogen/host encounter could influence the final outcome of many infections (31). We found that by reducing time response to infection to zero, immune priming prepares the host to face the infection, and the virus does not replicate anymore in the host.…”
Section: Discussionsupporting
confidence: 79%
“…Together, these two recent studies converge in illustrating Graham and Tate's conclusion that the sooner the immune system launches, the greater the chances the host has of survival (30). It is also consistent with recent systems biology approach suggesting that early pathogen/host encounter could influence the final outcome of many infections (31). We found that by reducing time response to infection to zero, immune priming prepares the host to face the infection, and the virus does not replicate anymore in the host.…”
Section: Discussionsupporting
confidence: 79%
“…The presence of high levels of apoptosis-related transcripts and activated CASP-3 protein strongly suggests that apoptosis is associated with enhanced viral protection of rag1 −/− zebra fish, possibly by eliminating viral-infected cells at an early stage of infection. In this regard, recent system biology approaches have confirmed that similar early pathogen/zebra fish crosstalks may explain the final outcome of many infections ( 93 ). In contrast, late apoptosis-dependent lysis of host cells favors viral spread, as described for several fish rhabdoviruses, including SVCV ( 92 , 94 96 ), which indicates that a prompt activation is crucial for apoptosis to exert its antiviral role during rhabdoviral infections.…”
Section: Discussionmentioning
confidence: 98%
“…While this review primarily focuses on the utility of larval zebrafish, adult zebrafish also have advantages as a model. For example, the adaptive immune response to fungal infection can be studied in adult zebrafish [138,139]. In fact, the earliest use of zebrafish for the study of C. albicans infection employed intraperitoneal injection of adult fish, which showed that many aspects of Candida infection in mice could be replicated in the zebrafish model [44].…”
Section: Unique Aspects Of the Zebrafish Toolbox: Infection Localimentioning
confidence: 99%